2018
DOI: 10.1016/j.conbuildmat.2018.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Compressive test of GFRP-recycled aggregate concrete-steel tubular long columns

Abstract: In order to alleviate the problem of growing construction waste and utilize the favorable material properties of fibre-reinforced polymer (FRP), a novel form of composites, FRP-recycled aggregate concrete-steel columns (FRSCs), was proposed based on hybrid FRP-concrete-steel double-skin tubular columns (DSTCs). The composite of FRSC consists an outer FRP tube and an inner steel tube with an annular area of recycled aggregate concrete (RAC) filled between both tubes. To further investigate the compressive behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…At present, large amount of research has been conducted on the axial compression performance of DSTCs (Elchalakani and Ma, 2017; Fanggi and Ozbakkaloglu, 2013; Ozbakkaloglu and Fanggi, 2014; Yu and Teng, 2013; Yu et al, 2017; Zhang et al, 2015), and the mechanical performance and the parametric influence of the composite column are well understood (Li et al, 2020; Ozbakkaloglu and Fanggi, 2015; Xiong et al, 2018; Zeng et al, 2018). Some studies address the splicing method of concrete-filled FRP tubular member (Chen and Wang, 2015; Helmi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At present, large amount of research has been conducted on the axial compression performance of DSTCs (Elchalakani and Ma, 2017; Fanggi and Ozbakkaloglu, 2013; Ozbakkaloglu and Fanggi, 2014; Yu and Teng, 2013; Yu et al, 2017; Zhang et al, 2015), and the mechanical performance and the parametric influence of the composite column are well understood (Li et al, 2020; Ozbakkaloglu and Fanggi, 2015; Xiong et al, 2018; Zeng et al, 2018). Some studies address the splicing method of concrete-filled FRP tubular member (Chen and Wang, 2015; Helmi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [26] tested hybrid DSTCs under lateral impact loading using a drop hammer testing facility and confirmed the excellent energy dissipation ability of hybrid DSTCs. Some variations of hybrid DSTCs were also investigated experimentally, including (1) use of light-weight concrete [28]; (2) use of recycled aggregate concrete [29]; (3) use of ribbed steel tubes [30]; (4) use of high-strength steel tubes [31]; (5) use of large-rupture-strain FRP tubes [32].…”
Section: Introductionmentioning
confidence: 99%
“…Since the invention of hybrid DSTCs (Teng et al, 2004, 2007), extensive experimental studies have been undertaken on their monotonic compressive behavior (e.g. Fanggi and Ozbakkaloglu, 2013; Ozbakkaloglu and Akin, 2012; Ozbakkaloglu and Fanggi, 2013; Peng et al, 2018; Yu, 2007; Yu et al, 2010, 2012, 2017; Zeng et al, 2018; Zhang et al, 2011, 2012, 2015, 2017; Zhao et al 2016; Zhou et al, 2017). The first-ever study of hybrid DSTCs was conducted by Teng et al (2004, 2007), in which the rationale for hybrid DSTCs and their expected advantages were explained.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al (2017) investigated the use of light-weight concrete in hybrid DSTCs and confirmed that hybrid DSTCs still performed with good ductility. Zeng et al (2018) applied recycled aggregate concrete for hybrid DSTCs, and the test results indicated that the bearing capacity of hybrid DSTCs with recycled aggregate concrete was smaller than these specimens with normal aggregates, whereas the ductility of hybrid DSTCs with recycled aggregate concrete was much higher than these specimens with normal aggregate concrete. Yu et al (2017) confirmed that the ductility of hybrid DSTCs could be significantly enhanced if the large-rupture-strain FRP tube was used.…”
Section: Introductionmentioning
confidence: 99%